Use Case Specification Using the SILABREQ Domain Specific Language - Savić, Dušan; Vlajić, Siniša; Lazarević, Saša; Antović, Ilija; Stanojević, Vojislav; Milić, Miloš; da Silva, Alberto Rodrigues (Computing and Informatics, 2016)
The software requirements engineering process is a part of a software development process and one of the key processes in software development. The elicitation, analysis, specification and validation of software requirements occur during the requirements engineering process. Use cases are used as a technique for functional system specification. Different notations can be used for a use case specification. In this paper, we present SilabReq Domain Specific Language (SilabReq DSL) for use case specification. On the one hand, we develop this language to describe the use cases in clear and precise way through the meta-model, and on the other hand to specify the use cases to be readable and understandable for all stakeholders in the software development project. This allows us to develop different transformations to get the structure and the behavior of the system from defined use cases. In this paper apart from the SilabReq DSL, we present some of these transformations.